FREQUENCY OF HEPATITIS B AND C IN PATIENTS UNDERGOING ELECTIVE SURGERY - Memon, Muhammad Rafique; Shaikh, Altaf Ahmed; Soomro, Aftab Ahmed; Arshad, Saima; Shah, Qarib Abbas (Journal of Ayub Medical College Abbottabad, 2010)
Background: Viral Hepatitis (HBV and HCV) is a major health problem affecting approximately two billion population worldwide. It is one of the single most important cause of chronic liver disease and hepato-cellular carcinoma in Pakistan and worldwide and is now spreading beyond endemic dimensions. This study was carried out to assess the frequency of Hepatitis B and C infection in patients undergoing elective surgical operations, and to evaluate the associated risk factors. Methods: This was a descriptive study, conducted at Surgical Department of Ghulam Muhammad Mahar Medical College Hospital, Sukkur, from April 2009 to March 2010. All patients who were admitted in the Surgical Department for elective surgical operations were included in the study. The patients were screened for HBsAg and Anti-HCV using immunochromatography (ICT) method. Those who were weak positive by ICT were further confirmed by ELISA. Results: Total 913 patients were admitted in Surgical Department during study period for elective operations and were screened for HBsAg and Anti-HCV. Out of these, 572 (62.65%) were male and 341 (37.34%) were female. Mean age of these patients was 40 years. After screening, 33 (3.61%) patients were found HBsAg positive and 117 (12.8%) were Anti-HCV positive, while 9 (0.98%) were positive for both. Hepatitis-B was found in 21 (2.3%) males and 12 (1.3%) females, and Hepatitis-C was found in 68 (7.44%) males and 49 (5.36%) female patients. Parenteral injections by quacks, previous surgery, blood transfusion and shaving by barbers were found to be the risk factors. Conclusion: Our message is: '˜Prevention is better than cure'. It is essential to prevent spread of Hepatitis B and C by screening every patient before surgery and counselling the patients. The doctors and paramedical staff must follow proper ethical practice ensuring use of sterile disposables where indicated and protecting patients and themselves from these viral infections. Keywords: Hepatitis-B, Hepatitis-C, Screening, Surgical patients